On the Unequal Inequality of Poor Communities - Elbers, Chris; Lanjouw, Peter F.; Mistiaen, Johan; Özler, Berk; Simler, Ken (World Bank, Washington, D.C., 2013)
Important differences exist between communities with respect to their needs, capacities, and circumstances. As central governments are not able to discern these differences fully, they seek to achieve their policy objectives by relying on decentralized mechanisms that use local information. However, household and individual characteristics within communities can also vary substantially. A growing theoretical literature suggests that inequality within communities can influence policy outcomes, and that this influence could be harmful or helpful, depending on the circumstances. Empirical investigations into the impact of inequality have, to date, largely been held back by a lack of systematic evidence on community-level inequality. The authors use household survey and population census data to estimate per capita consumption inequality within communities in three developing countries: Ecuador, Madagascar, and Mozambique. Communities are found to vary markedly from one another in terms of the degree of inequality they exhibit. The authors also show that there should be no presumption that inequality is less severe in poor communities. They argue that the kind of community-level inequality estimates generated in this paper can be used in designing and evaluating decentralized antipoverty programs.